Dukes A carcinoma after colonic interposition for oesophageal stricture. Issue 6 (June 1989) - Houghton, A D; Jourdan, M; McColl, I
Abstract : The management of caustic and peptic oesophageal strictures refractory to medical treatment and repeated dilatations continues to be a challenge. Colonic interposition with subtotal oesophagectomy is felt by many surgeons to be the best treatment. Complications in the short and long term are, however, frequent. We report a case of a colonic carcinoma originating in a colonic interposition and growing up into the oesophageal remnant.